Exogenous ALA applied on different plant parts promotes tomato fruit quality and GABA synthesis - Bai, Peng; Wang, Junwen; He, Yongmei; Feng, Junfang; Li, Juanli; Shang, Xingpan; Wu, Yue; Yu, Jihua; Tang, Zhongqi; Xie, Jianming (Frontiers in Nutrition, 2025)
IntroductionTomato fruit are rich in γ-aminobutyric acid (GABA), which lowers blood pressure and improves sleep. An increase in GABA content is important for enhancing the nutritional quality of tomato fruit.MethodsTo investigate the effects of 5-aminolevulinic acid (ALA) on fruit quality and GABA synthesis in greenhouse tomatoes, the tomato cultivar (Solanum lycopersicum cv. ‘184’) was used as an experimental material. During the fruit-setting period, root drenching with 0, 10, and 50 mg·L−1 ALA, foliar spraying with 0, 50, and 100 mg·L−1 ALA, and fruit surface spraying with 0, 100, and 200 mg·L−1 ALA were applied. The study investigated the application of exogenous ALA to different parts of the plant to determine the optimal ALA concentrations for each application site (10 mg·L−1 for root application, 100 mg·L−1 for foliar application, and 100 mg·L−1 for fruit surface application). Using the selected optimal ALA concentrations, tomatoes were used to study the effects of exogenous ALA application at different sites on fruit quality and GABA synthesis of greenhouse tomatoes.Results and discussionThe results demonstrated that exogenous ALA application to different parts of greenhouse-grown tomato plants substantially increased single-fruit weight by 42.37%–76.24%, soluble sugar content by 78.51%–94.52%, soluble solids by 9.09%–41.71%, soluble protein by 82.71%–241.05%, and ascorbic acid content by 1.31%–5.06% in mature tomatoes. And it reduced the organic acid content of the fruit by 12.81%–33.61%. Moreover, ALA applied at different parts of plants substantially enhanced the free amino acid content by 11.22%–16.50%, among them, umami amino acid content by 7.26%–20.13%. Besides, GABA content in mature tomato fruits was increased by 214.58%–433.32 across the different application parts. Exogenous ALA application at different sites regulates the activity of glutamate acid decarboxylase (GAD) and increases the content of glutamate for GABA synthesis pathway during tomato fruit development, thereby affecting the GABA content. In summary, exogenous ALA applied at different parts of tomato plants regulates the metabolism of amino acids and enhances the biosynthesis of GABA, which promotes the nutrient quality of the fruit.